Axial and helical thermally activated delayed fluorescence bicarbazole emitters: opposite modulation of circularly polarized luminescence through intramolecular charge-transfer dynamics. Issue 35 (25th August 2021) - Sumsalee, Patthira; Abella, Laura; Roisnel, Thierry; Lebrequier, Sabrina; Pieters, Grégory; Autschbach, Jochen; Crassous, Jeanne; Favereau, Ludovic
Abstract : The design of novel chiral donor–acceptor emitters based on C 2 -symmetric bicarbazoles is reported together with their photophysical and CPL properties, both displaying an interesting modulation as a function of the solvent polarity. Abstract : The rationalization of the molecular parameters that influence the intensity and sign of circularly polarized luminescence (CPL) for chiral emitters is a challenging task and remains of high interest for future chiral optoelectronic applications. In this report, we explore the design of novel chiral donor–acceptor structures based on C 2 -symmetric bicarbazole systems and compare the influence of the type of chirality, namely axial versus helical, and the electron withdrawing strength of the acceptor units on the resulting photophysical and CPL properties. By using carbonyl-based acceptors with both axial and helical electron donors, CP-Thermally Activated Delayed Fluoresence (TADF) can be obtained, whose efficiency depends on the dihedral angle between the carbazole moieties, related to the axial and helical chirality of the compounds. The latter also impacts the intensity of the CPL, which shows an opposite trend as a function of the polarity of the solvent, with a notably strong increase of the luminescence dissymmetry factor, g lum, for the helical donor–acceptor compounds related to a subtle reoarganization of the intramolecular charge-transfer process.